Pencatatan Al-Bai'u Di Rumah Makan Pantai Anyer Serang Banten - Adrianto; Sitorus, Chalid (Jurnal Landraad, 2024)
Al-bai’u is an exchange goods or exchange goods for money and Execution of trade contracts It requires the consent of both parties. Akad al-bai’u in restaurants Anyer Banten with the seller does not deliver list of pice of food to customers This research uses an approach qualitative and method Analysis normative-empirical of law research and answer issues that arise in the contract al-bai’u in restaurants The research results show that akad al-bai’u in restaurant is allowed, if akad in restaurant Anyer Banten This is done at the beginning, namely when the buyer has finished taking the desired menu So it's counting Price of food set before the buyer eats And the nature of payment in a direct way between sellers and buyers who meet face to face and Akad al-bai’u in restaurant Anyer Banten is in the form of debts and receivables which must be recorded as stated in the statement of Allah which is written in surah al baqarah ayat 282